Acute-On-Chronic Liver Failure: The Role of Prognostic Scores in a Single-Center Experience - Niewiński, Grzegorz (Med Sci Monit, 2020)
BACKGROUND: Acute-on-chronic liver failure (ACLF) is associated with multi-organ failure and high short-term mortality. We evaluated the role of currently available prognostic scores for prediction of 90-day mortality in ACLF patients. MATERIAL/METHODS: Fifty-five (M/F=40/15, mean age 60.0±11.1years) consecutive cirrhotic patients with severe liver insufficiency (mean MELD 28.4±9.0, Child-Pugh score – C-12) were enrolled into the study. MELD variants and SOFA, CLIF-SOFA, and CLIF-C scores were calculated, mortality predicting factors were identified, and clinical comparisons between ACLF and AD patients were performed. RESULTS: In total, 30 (55%) patients were transplanted (22 ACLF and 8 AD), and 20 (30%) died (19 ACLF and 1 AD). Five (9%) patients survived without liver transplantation (LT) (3 ACLF and 2 AD), and 3 transplant recipients died within 1 month. SOFA, CLIF-SOFA, CLIF-C OF, and INR were significantly associated with the incidence of 90-day mortality in competing risk regression analysis (all p<0.001). The model based on SOFA had the lowest BIC, with the optimal cut-off for 90-day mortality prediction ≥12, with the area under the receiver operating characteristic (AUROC) of 0.901 (95% CI 0.779–1.000; p<0.001), and corresponding incidence of transplantation rates of 85.5% and 11.8%, respectively (p<0.001). Of note, the important role of 24-h urine output is emphasized. CONCLUSIONS: In this series of ACLF patients, SOFA score outperformed the CLIF-C scores in predicting 90-day mortality. Multi-organ failure scores performed better in predicting patient mortality than conventional liver function assessment. LT is possible and remains effective in selected ACLF patients.